Electronic configuration of vanadium carbide (VC) - Fareed M. Mohammed; Sameh H. Salih; Abdulkader A. Hassan; Shalash A. Mohammed (Tikrit Journal of Pure Science, 2018)
In this paper we used renormalized free atom model to study the electronic configuration of vanadium carbide compound. The theoretical values were obtained after finding the values of each element separately and using the superposition model to find the best electronic arrangement. These results were compared with experimental values measured by using high energy (661.65 keV)ɣ-radiations from a 137Cs source. We observed  two things, first; if half the density of the electronic momentum of the compound is concentrated in vanadium we get the electronic order (2s1-2p1.5)C+(3d+5.5-4s1)V. second, if full the density of the electronic momentum of the compound is concentrated in vanadium we got the electron order (2s1-2p0)C+(3d+7-4s1)V .The best results out of these were when the full electron transfer from carbon to vanadium   occurs.